Endogamous Marriage in the Habaib Community a Social Engineering Perspective by Roscoe Pound - Silvia Yulianti; Ishaq Ishaq; Muhammad Faisol (The Eastasouth Journal of Social Science and Humanities, 2026)
Ideally, Indonesian marriage law promotes an open marital system that does not restrict partner selection based on lineage. In social reality, however, the Habaib community in Lumajang Regency continues to practice endogamous marriage grounded in patrilineal lineage preservation. This study addresses the gap between the ideal inclusiveness of marriage law and the persistence of exclusive endogamous practices. The research novelty lies in examining Habaib endogamous marriage through the perspective of Law as a Tool of Social Engineering proposed by Roscoe Pound, which remains underexplored in previous studies. This research employs a qualitative phenomenological field approach. Data were collected through in-depth interviews and documentation, and analyzed using source triangulation and Roscoe Pound’s social engineering legal theory. The findings reveal that: (1) endogamous marriage practices among the Habaib community follow two patterns arranged marriages from childhood and marriages within kinship without formal arrangement; (2) four main factors drive these practices, namely lineage preservation, matchmaking traditions, familial doctrination, and the principle of marital compatibility (kufu’); and (3) from a social engineering perspective, law functions to sustain endogamy through the interplay of public, social, and private interest.